2021
DOI: 10.3390/molecules26092410
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Study of Heterotrophically Grown Chlorella sp. Isolated from Wastewater in Northern Sweden

Abstract: There are numerous strains of Chlorella with a corresponding variety of metabolic pathways. A strain we previously isolated from wastewater in northern Sweden can grow heterotrophically as well as autotrophically in light and has higher lipid contents under heterotrophic growth conditions. The aims of the present study were to characterize metabolic changes associated with the higher lipid contents in order to enhance our understanding of lipid production in microalgae and potentially identify new compounds wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…This is comparable to the biomass produced in CKM by the Nordic Chlorella vulgaris strain in this study (1.42 ± 0.17 g L −1 ) and significantly (p‐value ≤0.05) lower than its biomass produced in PPS (1.82 ± 0.12 g L −1 ). The amount of biomass produced in PPS by Chlorella vulgaris is also higher than in municipal wastewater after 13 days (1.15 ± 0.06 g L −1 ; Ferro et al (2018) or 8 days (1.25 ± 0.9 g L −1 ; Nzayisenga and Sellstedt (2021) of cultivation. In a study on microalgal cultivation in liquid digestates from anaerobic digestion of pulp and paper sludge, it was shown that biomass concentrations of Chlorella vulgaris can be achieved between 2.02 and 2.91 g L −1 within 15 days, depending on the growth medium.…”
Section: Resultsmentioning
confidence: 92%
“…This is comparable to the biomass produced in CKM by the Nordic Chlorella vulgaris strain in this study (1.42 ± 0.17 g L −1 ) and significantly (p‐value ≤0.05) lower than its biomass produced in PPS (1.82 ± 0.12 g L −1 ). The amount of biomass produced in PPS by Chlorella vulgaris is also higher than in municipal wastewater after 13 days (1.15 ± 0.06 g L −1 ; Ferro et al (2018) or 8 days (1.25 ± 0.9 g L −1 ; Nzayisenga and Sellstedt (2021) of cultivation. In a study on microalgal cultivation in liquid digestates from anaerobic digestion of pulp and paper sludge, it was shown that biomass concentrations of Chlorella vulgaris can be achieved between 2.02 and 2.91 g L −1 within 15 days, depending on the growth medium.…”
Section: Resultsmentioning
confidence: 92%
“…Alcohols have a highly negative effect on metabolism, especially glycerol in microalgae. It has been reported that this compound inhibits the production of three metabolites, such as glucose-6-phosphate, fructose-6-phosphate, and glyceric acid-3-phosphate, key intermediates in carbon metabolism [ 42 ]. In addition to alcohols, the hexane extract contained higher concentrations of dimethyl sulfone and creatinine than the other extracts.…”
Section: Resultsmentioning
confidence: 99%
“…characterized the metabolic changes related to lipid biosynthesis to improve the understanding of lipid production in heterotrophically grown Chlorella sp. using metabolomics 87 . In the current study, GC‐MS based qualitative metabolomics was used to understand the metabolic imprints of C. saccharophila subjected to VLC and HC supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…using metabolomics. 87 In the current study, GC-MS based qualitative metabolomics was used to understand the metabolic imprints of C. saccharophila subjected to VLC and HC supplementation. Due to alternative derivatization, repetition of identical metabolites was observed in the raw data files; the relative abundance of such metabolites was totaled and the peaks were manually curated to obtain 23 metabolites.…”
Section: Metabolome Analysesmentioning
confidence: 99%